Mengungkap Sanksi Pelayanan Adat sebagai Sistem Pengendalian Internal Pemberian Kredit pada BUMDes - Krisnia, Putu Lia; Musmini, Lucy Sri (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This study aims to determine the system of granting credit to village-owned enterprises (BUMDes) Wira Kusuma Munduk Bestala village, an internal control system with sanctions for customary services and the implications of implementing customary sanctions as an internal control system in suppressing bad loans at BUMDes Wira Kusuma Munduk Bestala Village. In this study using qualitative methods with primary data and secondary data. The results of this study stated that (1) the credit granting system applied to BUMDes Wira Kusuma, namely credit is only given to Munduk Bestala villagers who have a KK and are married, with a loan ceiling of Rp 3.000.000 – Rp 15.000.000, past the stage of filling out the form credit application and verification, (2) an internal control system with customary service sanctions in granting credit in the form of non-administrative recommendation letter by kelian adat to customers whos experience bad credit when they hold their yadnya ceremony, and (3) implications with the implementation of adat service sanction able to increase customer awareness to pay credit so as to reduce the number of customers experiencing bad loans.